Feminist thought: A more comprehensive introduction - Tong, Rosemarie; Botts, Tina Fernandes (New York Routledge, 2024)
A classic resource on feminist theory, this updated sixth edition of Feminist Thought: A More Comprehensive Introduction offers a clear, comprehensive, and incisive introduction to the major traditions of feminist theory. This new edition explores in detail the wide spectrum of feminist thought, from liberal feminism, radical feminism, Marxist and socialist feminisms, women-of-color feminisms, global, postcolonial, and transnational feminisms, to psychoanalytic feminism, care-focused and maternal-focused feminisms, to ecofeminism, existentialist, poststructural, and postmodern feminisms.